Maternal serum levels of C-reactive protein at early pregnancy to predict fetal growth restriction and preterm delivery: A prospective cohort study - Roshan Nikbakht; Elham Karimi Moghadam; Zeinab Nasirkhani (Shahid Sadoughi University of Medical Sciences, 2020)
Background: A considerable evidence suggests that maternal inflammation dysregulation may play as a risk factor for both maternal and neonatal outcomes. Objective: The study's objectives were designed to evaluate the correlation between serum C-reactive protein (CRP) levels, as an inflammation factor, preterm delivery, and small for gestational age (SGA) births. Materials and Methods: This prospective cohort study was conducted on 120 singleton pregnant women with gestational age less than 20 wk. Maternal CRP serum concentration was measured before 20 wk gestation. Patients were followed-up until the delivery and final outcomes of pregnancy were recorded in terms of preterm delivery and SGA births. Results: Serum CRP levels in participants with normal fetuses and SGA births were 4.09 ± 1.35 mg/l and 6.04 ± 3.29 mg/l, respectively (p = 0.19), while in cases of preterm delivery, it was 9.63 ± 5.78 mg/l (p < 0.001). By using receiver operating characteristic (ROC) curve, serum CRP levels (cut-off point 5.27 mg/l, area 0.836) had acceptable diagnostic accuracy value in distinguishing preterm delivery (sensitivity (75%), specificity (86.1%), positive predictive value (37.5%), negative predictive value (96.87%), accuracy (85%)) and serum CRP levels (cut-off point 6.67 mg/l, area 0.673) in distinguishing SGA births (sensitivity (50%), specificity (91.2%), positive predictive value (23.07%), and negative predictive value (97.19%), and accuracy (89.16 %)). Conclusion: Higher maternal serum CRP levels measured early in pregnancy may associate with higher risk of preterm delivery and SGA.